PERAN KONSELING INDIVIDUAL DALAM PEMBINAAN KONSEP DIRI POSITIF PESERTA DIDIK - Zunidar Zunidar (STIT Al-Ittihadiyah Labuhanbatu Utara, 2021)
The implementation of individual counseling should be able to form a positive self-concept of students so that students can understand themselves and develop their potential. The purpose of this study was to determine the implementation of individual counseling services, the implementation of individual counseling in fostering positive self-concept of students and to determine the role of individual counseling in fostering positive self-concept of students at MTs Laboratorium UIN SU Medan. This type of research is qualitative research, which examines the role of the supervisor in overcoming student learning difficulties. Based on the research results, it can be argued that the implementation of individual counseling services at MTs Laboratorium UIN SU Medan through the stages of planning, implementation, evaluation, analysis of evaluation results, follow-up, and reports on the results of the implementation of individual counseling service activities. There are several factors that can influence the formation of students' self-concept in the madrasah, namely age, daily appearance, family environment, friends, activities and student aspirations. The implementation of individual counseling services has a role in forming students' self-concepts. Through individual counseling services, students are directed to various activities in study groups, directed to social interaction in school, so that students are able to know and recognize their abilities and potential so that they can develop for their future needs.